2021
DOI: 10.1002/fsn3.2580
|View full text |Cite
|
Sign up to set email alerts
|

Green tea aqueous extract (GTAE) prevents high‐fat diet‐induced obesity by activating fat browning

Abstract: The global prevalence of overweight and obesity has increased markedly, and obesity has become a serious health concern (Afshin et al., 2017). Moreover, obesity is a risk factor for the development of many diseases, including type-2 diabetes, nonalcoholic fatty liver disease, cardiovascular disease, and several cancer types among others (Hruby & Hu, 2015;Ren et al., 2021). Emerging evidence suggests the occurrence of pathogenic events in the development and progression of obesity-associated comorbidities, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…We found that insulin, AKT, and AMPK signalling were afected by HTE, resulting in modulation of the expression levels of lipid and glucose metabolism-related genes. It has been reported that tea or tea products can prevent HFD-induced obesity by several mechanisms, such as activating fat browning [33,34], modulating gut microbiota [35,36], and infuencing lipid metabolism [37]. Our study showed that HTE had signifcant efects on lipid metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…We found that insulin, AKT, and AMPK signalling were afected by HTE, resulting in modulation of the expression levels of lipid and glucose metabolism-related genes. It has been reported that tea or tea products can prevent HFD-induced obesity by several mechanisms, such as activating fat browning [33,34], modulating gut microbiota [35,36], and infuencing lipid metabolism [37]. Our study showed that HTE had signifcant efects on lipid metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…Nonetheless, green tea may regulate the PPAR/FGF21/AMPK/UCP1 pathway, which then enhance thermogenic cells induction by reprogramming the first phase of adipocyte differentiation ( Bolin et al, 2020 ). Furthermore, green tea aqueous extract is shown to promote browning markers in inguinal WAT ( Li et al, 2021 ). In line with this, the aqueous extract of green tea markedly increased PGC-1α activation.…”
Section: Plant-derived Natural Products As Anti-obesogenic Agentsmentioning
confidence: 99%